Efikasi Ekstrak Mitragyna speciosa (Kratom) terhadap Penyembuhan Ulkus Diabetik: Tinjauan Literatur - Edlin Edlin; Gusbakti Rusip; Maya Sari Mutia; Yolanda Eliza Putri Lubis (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Diabetic ulcers, particularly diabetic foot ulcers (DFUs), are chronic complications of diabetes mellitus characterized by persistent inflammation, oxidative stress, impaired angiogenesis, increased infection risk, and delayed tissue remodeling. Botanically derived adjuncts have gained attention because their mixed phytochemical profiles may act on several wound-healing pathways simultaneously. Mitragyna speciosa (kratom) is an alkaloid-rich Rubiaceae plant with reported anti-inflammatory, antioxidant, antimicrobial, and pro-regenerative activities. This review aimed to evaluate the current evidence on the potential role of Mitragyna speciosa extract in diabetic ulcer healing, distinguish kratom-specific evidence from broader botanical context, and identify key knowledge gaps that must be addressed before clinical translation. Methods: A PRISMA-style systematic review was conducted using an internet search engine, which returned 521 records. Records were screened against predefined population, intervention, comparator, outcome, study-design, and attribution criteria. Eight sources met the eligibility criteria and were synthesized qualitatively. Results: No clinical trial, observational study, or in vivo diabetic-wound study directly compared kratom extract with standard wound care. Kratom-specific evidence was limited to in vitro and formulation studies. The available in vitro synthesis reported suppression of tumor necrosis factor-alpha, interleukin-6, cyclooxygenase-2, 5-lipoxygenase, nitric oxide, and reactive oxygen species, as well as stimulation of cell migration and angiogenesis. A topical spray film-forming kratom formulation has been developed, but efficacy data are not yet available. Broader systematic reviews indicate that botanical adjuncts may improve DFU healing outcomes, but these reviews did not include kratom. Current evidence supports biological plausibility but does not establish comparative effectiveness. Standardized kratom formulations require in vivo validation, dose-response assessment, safety evaluation, and adequately powered randomized clinical trials before any clinical recommendation can be made.